INTERVENSI LEVEL KELOMPOK: MANAJEMEN KONFLIK DALAM ORGANISASI PERBANKAN LITERATUR REVIEW - Alfi Ari Ardyansah; Heaven Alicya Hidayah Putri; Yongky Pratama; Raja Karomallahu Wajha (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Digital transformation in the banking sector increases work complexity, leading to role conflict and employee work stress. This study aims to map conflict management strategies in banking organizations through a systematic literature review (SLR) approach of 34 relevant references, including classic textbooks and scientific articles from 2019–2025. The study results indicate that organizational conflict is influenced by various factors, such as ineffective leadership, role ambiguity, and high work demands, which contribute to declining employee performance. Furthermore, aspects of organizational behavior such as suboptimal communication, differing interests, and work stress contribute to increasing conflict intensity in the banking environment. On the other hand, the implementation of good corporate governance (GCG), human resource management strategies, and the use of the Objectives, Goals, Strategies, and Measures (OGSM) framework have been shown to be effective in managing conflict constructively. Group-based interventions such as team building also play a role in increasing interpersonal trust and teamwork coordination. These findings confirm that integrated and adaptive conflict management is key to maintaining organizational stability and improving employee performance amidst digital transformation. This research is expected to provide conceptual and practical contributions to the development of conflict management policies in the banking sector.